Electrochemical etching technique for analyzing the shape and spatial arrangement of graphite inclusions in as‑cast and plastically deformed cast iron - A. I. Pokrovsky (Литьë и металлургия, 2025)
The technique for revealing the shape and spatial arrangement of graphite inclusions in the structure of cast iron and the scheme of the corresponding device are proposed. The method consists in gradual electrochemical dissolution (etching) of the outer layer of the metal matrix of the cast iron sample in the electrolyte. The specimen serves as an anode and a hollow cylinder as a cathode. The composition of the electrolyte, electrode material, sample shape, sample‑to‑cathode size ratio, and electrical parameters of the etching process are proposed. These parameters are selected in such a way that the graphite inclusions do not dissolve but remain intact, partially or completely exposed and protruding above the surface of the metal matrix. This situation makes graphite inclusions more accessible for studying their morphology using scanning electron microscopy. Method is most effective for revealing the structure of branched and elongated graphite inclusions, for example, for ductile cast iron subjected to hot plastic deformation. With the help of this technique the fact of plastic flow of brittle graphite inclusions during hot extrusion of cast specimens is proved. It is shown that the resulting spindle‑shaped graphite structure is a solid conglomerate and does not crumble into powder, as previously thought. It was found that the most intense plastic flow of graphite (with the maximum degree of deformation) occurs primarily in the surface layer. In the central part of the elongated graphite inclusion, weakly deformed or undeformed nuclei of characteristic spherical shape are preserved. It is shown that dissolution of the metal matrix occurs in stages. The ferrite component of pearlite dissolves first and then the cementite inclusions, because cementite has a more positive electrode potential than ferrite. Therefore, this technique, in addition to revealing the morphology of graphite inclusions, also makes it possible to analyze the spatial arrangement of cementite plates in pearlite.